Use of Humidified High Flow Nasal Oxygen in Community Palliative Care: A Case Report - Stephen Bode; Graham Grove (Palliative Medicine Reports, 2020)
Breathlessness is a distressing symptom that is often seen in palliative care patients with respiratory failure and it can make care in the home setting difficult. Humidified High Flow Nasal Oxygen is a relatively new intervention for respiratory failure, but it has not been researched greatly in a palliative care setting. One device with the capacity to deliver high flow humidified oxygen to spontaneously breathing patients is the myAIRVO2 humidifier.1 The myAIRVO2 is a humidifier with an integrated flow generator that delivers warmed and humidified respiratory gases to a spontaneously breathing patient.1 The following case report describes how the technology was used at home for symptom control in a 76 year old patient with severe chronic obstructive pulmonary disease with associated pulmonary hypertension. The patient was successfully discharged from hospital and managed at home using high-flow nasal oxygen for approximately one month up until his death. In this last month of life, he reported that he was more comfortable on high-flow nasal oxygen than on traditionally-administered oxygen. Humidified High Flow Nasal Oxygen is potentially beneficial to aid in symptom control for palliative care patients in an inpatient and community setting.